Postavení hydrochlorothiazidu mezi thiazidovými a thiazidům podobnými diuretiky - Slíva, Jiří (Vnitrni lekarstvi, 2018)
Thiazide and thiazide-like diuretics are an important group of drugs used in the treatment of essential arterial hyper-tension. While their beneficial therapeutic effect in monotherapy is evident, they are increasingly used in fixed combinations, particularly with ACE inhibitors or sartans. The aim of this article was to summarize the current status of hydrochlorothiazide and compare its effects with other substances in this subgroup of diuretics.Key words: diuretics - HCTZ - hydrochlorothiazide - hypertension - chlorthalidone - indapamide - thiazide.
Keywords: Antihypertensive Agents; Hypertension; hypertenze; lidé; Indapamide; antihypertenziva; chlorthalidon; Chlorthalidone; indapamid; Diuretics; hydrochlorthiazid; Humans; diuretika; Hydrochlorothiazide